Studies on mosquito biting risk among migratory rice farmers in rural south-eastern Tanzania and development of a portable mosquito-proof hut. (December 2016) - Swai, Johnson; Finda, Marceline; Madumla, Edith; Lingamba, Godfrey; Moshi, Irene; Rafiq, Mohamed; Majambere, Silas; Okumu, Fredros
Abstract Background Subsistence rice farmers in south-eastern Tanzania are often migratory, spending weeks or months tending to crops in distant fields along the river valleys and living in improvised structures known asShamba huts, not fully protected from mosquitoes. These farmers also experience poor access to organized preventive and curative services due to long distances. Mosquito biting exposure in these rice fields, relative to main village residences was assessed, then a portable mosquito-proof hut was developed and tested for protecting these migratory farmers. Methods Pair-wise mosquito surveys were conducted in four villages in Ulanga district, south-eastern Tanzania in 20 randomly-selectedShamba huts located in the distant rice fields and in 20 matched houses within the main villages, to assess biting densities andPlasmodium infection rates. A portable mosquito-proof hut was designed and tested in semi-field and field settings againstShamba hut replicas, and actualShamba huts. Also, semi-structured interviews were conducted, timed-participant observations, and focus-group discussions to assess experiences and behaviours of the farmers regarding mosquito-bites and the mosquito-proof huts. Results There were equal numbers of mosquitoes inShamba huts and main houses [RR (95% CI) 27 (25.1–31.2), and RR (95% CI) 30 (27.5–33.4)], respectively (P > 0.05). Huts having >1 occupant had more mosquitoes than those with just one occupant, regardless of site [RR (95% CI) 1.57 (1.30–1.9), P < 0.05]. Open eaves [RR (95% CI) 1.15 (1.08–1.23), P < 0.05] and absence of window shutters [RR (95% CI) 2.10 (1.91–2.31), P < 0.05] increased catches of malaria vectors. AllAnopheles mosquitoes caught were negative forPlasmodium . Common night-time outdoor activities in the fields included cooking, eating, fetching water or firewood, washing dishes, bathing, and storytelling, mostly between 6 and 11 p.m., when mosquitoes were also biting most. The prototype hut provided 100% protection in semi-field and field settings, while blood-fed mosquitoes were recaptured inShamba huts, even when occupants used permethrin-impregnated bed nets. Conclusion Though equal numbers of mosquitoes were caught between main houses and normalShamba huts, the higher proportions of blood-fed mosquitoes, reduced access to organized healthcare and reduced effectiveness of LLINs, may increase vulnerability of the itinerant farmers. The portable mosquito-proof hut offered sufficient protection against disease-transmitting mosquitoes. Such huts could be improved to expand protection for migratory farmers and possibly other disenfranchised communities.